The influence of amphiphilic carbosilane dendrons on lipid model membranes - Wrobel, Dominika; Edr, Antonin; Zemanova, Eliska; Strašák, Tomáš; Semeradtova, Alena; Maly, Jan (Chemistry and physics of lipids, 2023)
Amphiphilic dendrons represent a relatively novel class of molecules which may show many unique properties suitable for applications in a field of molecular biology and nanomedicine. They were frequently studied as platforms suitable for drug delivery systems as were, e.g. polymersomes or hybrid lipid-polymer nanoparticles. Recently, natural extracellular lipid vesicles (EVs), called exosomes (EXs), were shown to be a promising candidate in drug delivery applications. Formation of hybrid exosome-dendron nanovesicles could bring benefits in their simple conjugation with selective targeting moieties. Unfortunately, the complex architecture of biological membranes, EXs included, makes obstacles in elucidating the important parameters and mechanisms of interaction with the artificial amphiphilic structures. The aim of the presented work was to study the interaction of two types of amphiphilic carbosilane dendritic structures (denoted as DDN-1 and DDN-2) suitable for further modification with streptavidin (DDN-1) or using click-chemistry approach (DDN-2), with selected neutral and negatively charged lipid model membranes, partially mimicking the basic properties of natural EXs biomembranes. To meet the goal, a number of biophysical methods were used for determination of the degree and mechanisms of the interaction. The results showed that the strength of interactions of amphiphilic dendrons with liposomes was related with surface charge of liposomes. Several steps of interactions were disclosed. The initialization step was mainly coupled with amphiphilic dendrons - liposomes surface interaction resulting in destabilization of large self-assembled amphiphilic dendrons structures. Such destabilization was more significant with liposomes of higher negative charge. With increasing concentration of amphiphilic dendrons in a solution the interactions were taking place also in the hydrophobic part of bilayer. Further increase of nanoparticle concentration resulted in a gradual dendritic cluster formation in a lipid bilayer structure. Due to high affinity of amphiphilic dendrons to model lipid bilayers the conclusion can be drawn that they represent promising platforms also for decoration of exosomes or other kinds of natural lipid vehicles. Such organized hybrid dendron-lipid biomembranes may be advantageous for their subsequent post-functionalization with small molecules, large biomacromolecules or polymers suitable for targeted drug-delivery or theranostic applications.
Keywords: Amphiphilic dendrons; silany; Nanoparticles; Model membranes; membránové potenciály; liposomy; Membrane Potentials; nanočástice; Hybrid liposomes; Self-assembling; Dendrimers; Silanes; Anisotropy; kalorimetrie; Calorimetry; dendrimery; Liposomes; anizotropie